Malaria card: an empowering tool for patients and for epidemiological recording - Manju Rahi; Peeyush Mittal; Jaspreet Kaur; Amit Sharma (Inishmore Laser Scientific Publishing Ltd, 2021)
Malaria places a substantial burden on the tropical and subtropical regions of the world. World Malaria Report 2020 showed that the progress in global malaria control has come to a plateau. On the other hand, India has shown considerable progress in reducing its malaria burden. Malaria surveillance system mainly depends upon health workers who are also involved with other national health programs. Community participation can play significant role in success of any control/elimination programme. Epidemiological monitoring and record keeping of disease occurrence and control programmes is important. We have designed and proposed a simple booklet called "*Malaria card*" which when deployed in the community, can potentially result in improved malaria tracking and record-keeping. The malaria card like immunization card for under-five children, can be utilized to capture information on important aspects of malaria and co-morbidities. It will help communities in maintaining their own record and also will give easy access to health care workers to episodes of malaria and for epidemiological tracking.